Review of the phyline plant bug tribe Auricillocorini from Asia, with descriptions of a new genus and nine new species from Japan, Nepal and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae) - Yasunaga, Tomohide (Zootaxa, 2012)
The phyline plant bug tribe Auricillocorini from Asia is reviewed; 23 species in 6 genera are shown to occur in the Indo-Pacific. A new genus, Artchawakomius, is proposed to accommodate two undescribed, morphologically novel species from Thailand. Nine new species are described from Japanese Ryukyus, Nepal or Thailand: Artchawakomius moteus, A. pius, Cleotomiris miyamotoi, C. yamadakazi, Cleotomiroides tobii, Wygomiris kaliyahae, W. nanae, W. ramae and Zaratus hidekun. Photographic images of living individuals are provided for all new species. The female genitalic structures, which have not been employed for classification of the Auricillocorini, are described and figured for six available species. Wygomiris indochinensis Schuh, known thus far only from Laos, is found also in Thailand; the female is reported for the first time. A checklist of Auricillocorini and a discussion on phylogenetic relationships for all known genera are provided.